Theoretical interpretation of scanning probe images of molecules on surfaces - Abdur Rashid, Mohammad (2017)
Scanning tunnelling microscopy (STM) and atomic force microscopy (AFM) can produce images of molecules with extremely high resolution. However, Claims that dynamic force microscopy has the capability to resolve intermolecular bonds in real space continue to be vigorously debated. Several studies have now shown that tip flexibility, especially at very close tip-sample separations, is responsible for the striking intra- and intermolecular resolution observed with various scanning probe microscopy techniques. The apparent intermolecular features can be observed with dynamic force microscopy even when no bonding interaction is present, suggesting that such features are in fact an artefact and cannot be interpreted as a real-space image of an intermolecular bond.